The Bottom-Up Rise Strength Transfer in Elderly After Endurance and Resistance Training: The BURST - Pietrangelo, Tiziana; Bondi, Danilo; Kinel, Edyta; Verratti, Vittore (Frontiers in Physiology, 2019)
The phenomenon of strength gain is highly relevant for sarcopenia and clinical aspect linked to aging. Recent advancements drive the interest toward the exercise-related cross-talk between distant tissues. We demonstrated the cross-talk between lower and upper limbs, we named the Bottom-Up Rise Strength Transfer (BURST), mainly linked to endurance training. In our opinion, this effect can be mainly related to systemic factors, likely circulating myokines and extracellular vesicles (recently defined in terms of “exerkines” and “exersomes”) whit an eventual concomitant reduction of a sub-clinical chronic inflammation. The neuronal mechanisms, even if to our sight less likely involved in this adaptation, need to be deeply investigated. Further studies are needed to better characterize the exercise-related BURST, concerning the specificity of different protocols and the underlying physiological mechanisms.